An empirical analysis of the factors that influence infrastructure project financing by banks in select Asian economies - Vivek Rao (Asian Development Bank (ADB), 2018)
A recent Asian Development Bank publication estimates the large infrastructure financing requirement in Asia for the period 2016-2030, which establishes the strong need to encourage private sector participation to meet investment requirements. This paper analyzes a critical aspect of expanding private finance to infrastructure by examining the role of bank lending to public-private partnership (PPP) projects through the project finance modality. The key empirical results suggest that project financing by banks to infrastructure PPP projects is still in its infancy in several Asian markets, and banks are guided more by macroeconomic factors and by the strength of their balance sheets. The key policy implications to unlock bank finance for infrastructure PPP projects lie in reducing macroeconomic risk factors and having well-capitalized banks. The latter assumes significance, given the higher capital requirements that banks are expected to fulfill, following the adoption of Basel III capital standards.
Keywords: G21; G32; H41; H54; 330; project finance; bank lending; infrastructure; public-private partnership